2021
DOI: 10.1111/psyp.13885
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of transcutaneous auricular vagus nerve stimulation on reversal learning, tonic pupil size, salivary alpha‐amylase, and cortisol

Abstract: Exposure therapy, i.e., repeated exposure to fear-provoking stimuli, is an effective cognitive behavioral therapy strategy for the treatment of anxiety and trauma-related disorders (Hofmann & Smits, 2008). Extinction learning is considered a major mechanism for the reduction of fear during exposure, as it involves learning that the stimulus previously appraised as threatening no longer leads to the feared outcome (Lonsdorf et al., 2017). The predominant view is that extinction hereby results in a new memory (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
48
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 89 publications
7
48
3
Order By: Relevance
“…The null results on pre-stimulus baseline pupil size and tonic pupil size at rest are in line with previous studies assessing the effect of taVNS on tonic measures of pupil size (Borges et al, 2021;Burger, Van der Does, et al, 2020;D'Agostini et al, 2021;Keute et al, 2019;Warren et al, 2019). Instead, we could not replicate the preliminary positive findings on cortisol (D'Agostini et al, 2021;Warren et al, 2019). The lack of an effect on sAA secretion is also in contrast with the initial evidence in favor of a sAA modulation by taVNS (Ventura-Bort et al, 2018; Warren Note: The Bayes factor (BF 01 ) was estimated using the Bayesian Information Criteria of models output (Wagenmakers, 2007; BF 01 = exp((BIC Hi − BIC H0 )/2)).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The null results on pre-stimulus baseline pupil size and tonic pupil size at rest are in line with previous studies assessing the effect of taVNS on tonic measures of pupil size (Borges et al, 2021;Burger, Van der Does, et al, 2020;D'Agostini et al, 2021;Keute et al, 2019;Warren et al, 2019). Instead, we could not replicate the preliminary positive findings on cortisol (D'Agostini et al, 2021;Warren et al, 2019). The lack of an effect on sAA secretion is also in contrast with the initial evidence in favor of a sAA modulation by taVNS (Ventura-Bort et al, 2018; Warren Note: The Bayes factor (BF 01 ) was estimated using the Bayesian Information Criteria of models output (Wagenmakers, 2007; BF 01 = exp((BIC Hi − BIC H0 )/2)).…”
Section: Discussionsupporting
confidence: 91%
“…As taVNS might still affect CVA indirectly via central pathways (Murray et al, 2016), we further explored the effect of taVNS on CVA. In addition, one study (D'Agostini et al, 2021) out of three (Borges et al, 2020(Borges et al, , 2021 found respiratory rate to significantly decrease from prior to end of stimulation in the taVNS compared to the sham group. Replication of such effect in the current study seems important as respiratory rate could potentially be employed as a future marker of successful taVNS.…”
Section: Introductionmentioning
confidence: 99%
“…While pupil dilation has been considered as a potential biosensor for successful VNS, particularly following findings in animal model studies [62,63], our results show no effect of taVNS on resting pupil size in humans in line with a number of other studies [27][28][29]64]. There are several reasons why we may have failed to detect pupil dilation changes under taVNS relative to the sham condition: (1) the transcutaneous protocol used was insufficient to stimulate the vagus nerve sufficiently, perhaps due to the stimulation parameters (pulse width, frequency and amplitude) which still need further optimization [6,65]; however our current study did find both eye-gaze and oxytocin concentration changes after the stimulation, which suggest that the taVNS parameters chosen do have functional effects; (2) the procedure used to measure pupil dilation (i.e., the way we defined baseline pupil size and selection of time points) might also have influenced the results.…”
Section: Discussionsupporting
confidence: 89%
“…While one study reported an increase in pupil dilation during tVNS, which was not observed in sham stimulation [52], another study demonstrated an increased pupil size only for the left eye under specific scotopic illumination and stimulation conditions [53]. In contrast, two recent studies did not find any changes in pupillary responses and cardiac vagal activity associated with active tVNS during cognitive tasks [54,55]. Using electroencephalography, one study showed an increased attenuation of alpha oscillations during tVNS [53], while another reported a greater power in the delta band frequencies [56].…”
Section: Discussionmentioning
confidence: 98%